2014
DOI: 10.1037/ebs0000011
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary domain-specific risk scale.

Abstract: We present a psychometric scale that assesses risk-taking in 10 evolutionary content domains: between-group competition, within-group competition, status-power, environmental exploration, food selection, food acquisition, parent-offspring conflict, kinship, mate attraction, and mate retention. We report on three studies that evaluate the scale’s validity and consistency for a sample of 1,326 participants who rated their likelihood of engagement in, the perceived riskiness of, and the benefit associated with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 52 publications
1
34
0
1
Order By: Relevance
“…The best model also shows domaindifferences in the risk-taking propensities (post-hoc comparisons, see Table A1 in the Appendix), similar to previous findings (Wilke et al, 2014). The results show no significant overall gender difference (Δ f-m = 0.055, p = .478), but differences in certain domains, which is contrary to the common notion that men are consistently more risk-taking than women (Byrnes et al, 1999).…”
Section: Predictors Of Domain-specific Risky Choicesupporting
confidence: 82%
See 1 more Smart Citation
“…The best model also shows domaindifferences in the risk-taking propensities (post-hoc comparisons, see Table A1 in the Appendix), similar to previous findings (Wilke et al, 2014). The results show no significant overall gender difference (Δ f-m = 0.055, p = .478), but differences in certain domains, which is contrary to the common notion that men are consistently more risk-taking than women (Byrnes et al, 1999).…”
Section: Predictors Of Domain-specific Risky Choicesupporting
confidence: 82%
“…In the first session and before the choice task, participants were familiarized with the ten behaviors and it was made clear that each behavior might have both costs and benefits. Participants then reported the subjective size of the costs and benefits of engaging in all the behaviors 1 , beliefs about the probabilities of these benefits and costs 2 , filled in a domain-specific risk attitude scale (ERS, Wilke et al, 2014), and reported demographic and life-history data (not reported here). In the choice task, which was presented as "game of daily life", participants decided about engaging in or refraining from behaviors in ten domains, such as work weekends to outperform your colleagues to be considered for a promotion (within-group competition domain).…”
Section: Methodsmentioning
confidence: 99%
“…To assess this, we utilize Study 4. In this study, we have available measures of formidability, SDO, and individual variation in willingness to take risks across 10 different domains that reflect significant problems over human evolutionary history (The Evolutionary Risk Scale; Wilke et al, ). Specifically, these domains are: between‐group competition, within‐group competition (specifically, taking on leadership roles), status and power seeking, environmental exploration, food selection, food acquisition, parent‐offspring conflict, helping kin, mate attraction, and mate retention.…”
Section: Formidability and Conflicts In Humans And Other Animalsmentioning
confidence: 99%
“…This result was puzzling as the evolution of risk-sensitive responses for men who already have a sexual partner should favor distancing and decrease their mating efforts. For instance, Wilke with coauthors [78] had shown that, in the domains of mate retention and attraction, single individuals gave higher scores on propensity of risk-taking behavior than those who were married or in a committed relationship. Contradicting to the Wilke with coauthors study, our results have shown that coupled men demonstrated an even higher level of sociosexual activity than single men.…”
Section: Discussionmentioning
confidence: 99%